EXPERIMENTAL STUDY AND SIMULATION ON AXIAL COMPRESSION OF LAMINATED CELLULAR CYLINDRICAL SHELL (MT) - HE Pu; DENG QingTian; LI XinBo; SONG XueLi (Jixie qiangdu, 2023)
Experimental tests and finite element simulation methods were used in this article. The bearing loads and deformation failure modes of laminated cellular cylindrical shell under axial compression loads were studied. Two kinds of cellular units, regular hexagon and re-entrant, were studied. The influence of different heights, diameters and thicknesses on the axial bearing loads were discussed with laminated cellular cylindrical shell. It is concluded that the axial compression performance of re-entrant cylindrical shell is better than regular hexagonal cylindrical shell. The buckling deformation modes of laminated cellular cylindrical shell under axial compression were analyzed. In addition, the material parameters obtained by the test were used to simulate the experimental results, compared the deformation modes and compression performance of simulation and experimental results.